2009
DOI: 10.1007/s11814-009-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of ionic liquids as mobile phase additives and surface-bonded stationary phase in liquid chromatography

Abstract: Ionic liquids (ILs) have gained wide recognition as novel solvents in chemistry. Their application in analytical chemistry, especially in separating analytes, is warranted due to their unique properties such as negligible vapor pressure, good thermal stability, tunable viscosity and miscibility with water and organic solvents, as well as good extractability for various organic compounds and metal ions. Recently, some new chromatographic separation media, formed by combining ILs on silica and polymer surface us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The replacement of conventional solvents with ionic liquids is the subject of many research projects around the world. Ionic liquids have been applied in various fields such as in enzymatic reactions, electrochemistry, pharmaceuticals, liquid extraction, , solvent extraction, solar cells and batteries, , liquid chromatography, gas chromatography, electrophoresis, , and sensors …”
Section: Introductionmentioning
confidence: 99%
“…The replacement of conventional solvents with ionic liquids is the subject of many research projects around the world. Ionic liquids have been applied in various fields such as in enzymatic reactions, electrochemistry, pharmaceuticals, liquid extraction, , solvent extraction, solar cells and batteries, , liquid chromatography, gas chromatography, electrophoresis, , and sensors …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, ionic liquids and their advantages have received great attention recently as a green solvent in various chemical industries [3,4]. In addition, ionic liquids have been widely considered as alternatives to classical organic solvents and have been applied in electrochemistry, organic synthesis, liquid phase extraction and catalysis for clean technology [5]. Recent researches have shown that ionic liquids are used in membrane-based systems for separation processes and liquid-liquid separation processes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] According to literatures, 21,22 a butylimidazolium-based phase was shown to exhibit remarkable reversed-phase retention properties emanating from the imidazolium ring. Firstly, 6.0 g 1-chlorobutane and 4.2 g imidazole were added into a dry round bottom flask containing a magnetic stir bar, and then 50.0 mL toluene was added as solvent.…”
Section: Preparation Of Ils-based Monolithic Cartridgementioning
confidence: 99%